2019
DOI: 10.1007/s11135-019-00910-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of military expenditures and economic growth: lessons for Romania

Abstract: This paper examines the correlation between public policies in the field of military expenditures and economic growth in Romania. The research is built upon the vast literature focused on the field of public policies and economic growth. Whereas economic growth became one of the most dynamic areas in economics, this correlation will consider the determinants of the real sector development through economic phenomenon modeling. The impact of military expenditures on growth is analysed for Romania, using annual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…The findings of this study are consistent with the study carried out by Knight et al (1996), Hou andChen (2013), andD'Agostino et al (2017), and Saba and Ngepah (2019). While, our results are in contrast with the findings of Narayan and Singh (2007), Feridun et al (2011), Farzanegan (2014, Sheikh et al (2017), andLobont et al (2019), as these studies yield positive relationship between military expenditures and economic growth, also quite consistent with the illustration of the Keynesian school of thought. Mostly military expenditure is unproductive in developing countries.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of this study are consistent with the study carried out by Knight et al (1996), Hou andChen (2013), andD'Agostino et al (2017), and Saba and Ngepah (2019). While, our results are in contrast with the findings of Narayan and Singh (2007), Feridun et al (2011), Farzanegan (2014, Sheikh et al (2017), andLobont et al (2019), as these studies yield positive relationship between military expenditures and economic growth, also quite consistent with the illustration of the Keynesian school of thought. Mostly military expenditure is unproductive in developing countries.…”
Section: Resultssupporting
confidence: 93%
“…Several prior studies have drawn findings that support the Keynesian military view of the positive influence of military expenditure on national output (Benoit, 1978;Khalid and Noor, 2018;Raju and Ahmed, 2019). In a study conducted by Lobont et al (2019), it is ascertained that military spending has several positive effects on capital, labor, growth, and the effectual use of available resources in the economy as a whole.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most empirical studies used panel analysis to test the cointegration and causality between military spending and GDP or normal debt (Lobont et al, 2019). For example, cointegration and error correction have been used to explore this relationship.…”
Section: Methodsmentioning
confidence: 99%
“…And after the completion of research, Hou and Chen (2013) concluded and remarked that an arms expense has an indirect and significant impact on economic growth in the sample countries. Lobont, Glont, Badea, and Vatavu, (2019) did research related to the association among military expenses and economic growth in Romania. And this research is done by using annual data from the period of 1991-2016.…”
Section: Impact Of Military Expenditure On Economic Growth and Employmentioning
confidence: 99%